2022
DOI: 10.1029/2022gl099583
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Water Flux in California's Central Valley and Its Source Watershed From Space Geodesy

Abstract: produce alternating periods of drought and years of heavy precipitation in California (Cayan et al., 1999) (Figure S1 in Supporting Information S1). Anthropogenic greenhouse gases have warmed Earth by 0.9°C since 1950, creating harsher droughts and fiercer flooding in the west U.S. (IPCC, 2021). Severe drought struck California from October 2011 to October 2015 (Griffin & Anchukaitis, 2014;Swain et al., 2014). Precipitation was low and temperature high during the 4 years (PRISM Climate Group, 2017). Snow accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…The TWS inferred using the Green's function and SBF methods show good agreement with the GRACE/GFO and hydrologic models, but there are differences in the spatial and temporal patterns in some regions [26]. Other recent studies focused on obtaining more reliable TWS estimates through the joint inversion of the GNSS and GRACE/GFO in the CONUS [27][28][29] and China [26,[30][31][32]. Adusumilli et al [27] and Carlson et al [29] pointed out that the integration of GNSS and GRACE produces a higher spatiotemporal resolution than does GRACE alone.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The TWS inferred using the Green's function and SBF methods show good agreement with the GRACE/GFO and hydrologic models, but there are differences in the spatial and temporal patterns in some regions [26]. Other recent studies focused on obtaining more reliable TWS estimates through the joint inversion of the GNSS and GRACE/GFO in the CONUS [27][28][29] and China [26,[30][31][32]. Adusumilli et al [27] and Carlson et al [29] pointed out that the integration of GNSS and GRACE produces a higher spatiotemporal resolution than does GRACE alone.…”
Section: Introductionmentioning
confidence: 83%
“…According to the elastic deformation theory [5,28,56,57], the relationship between vertical displacements and TWS in the EWH reads:…”
Section: Gnss Inversion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the enactment of the Sustainable Groundwater Management Act in 2014, which aims to combat overdraft in the SJV, groundwater depletion is still occurring. Specifically, Argus et al (2022) concluded that the southern SJV lost 1.5 ± 0.4 km 3 yr –1 during 2006–2021 . Similarly, Liu et al (2022) observed a decrease in groundwater storage (2.55 ± 0.60 km 3 yr –1 ) in the southern SJV over the present drought (2019–2022) .…”
Section: Discussionmentioning
confidence: 98%
“…Specifically,Argus et al (2022) concluded that the southern SJV lost 1.5 ± 0.4 km 3 yr −1 during 2006−2021 70. Similarly, Liu et al (2022) observed a decrease in groundwater storage (2.55 ± 0.60 km 3 yr −1 ) in the southern SJV over the present drought (2019−2022) 71.…”
mentioning
confidence: 96%